Quantitative Nano‐amperometric Measurement of Intravesicular Glutamate Content and its Sub‐Quantal Release by Living Neurons - Yang, Xiao‐Ke; Zhang, Fu‐Li; Wu, Wen‐Tao; Tang, Yun; Yan, Jing; Liu, Yan‐Ling; Amatore, Christian; Huang, Wei‐Hua (Angewandte Chemie International Edition, 2021)
Quantitative measurements of intravesicular glutamate (Glu) and of transient exocytotic release contents directly from individual living neurons are highly desired for understanding the mechanisms (full or sub‐quantal release?) of synaptic transmission and plasticity. However, this could not be achieved so far due to the lack of adequate experimental strategies relying on selective and sensitive Glu nanosensors. Herein, we introduce a novel electrochemical Glu nanobiosensor based on a single SiC nanowire that can selectively measure in real‐time Glu fluxes released via exocytosis by large Glu vesicles (ca. 125 nm diameter) present in single hippocampal axonal varicosities as well as their intravesicular content before exocytosis. These measurements revealed a sub‐quantal release mode in living hippocampal neurons, viz., only ca. one third to one half of intravesicular Glu molecules are released by individual vesicles during exocytotic events. Importantly, this fraction remained practically the same when hippocampal neurons were pretreated with L‐Glu‐precursor L‐glutamine, while it significantly increased after zinc treatment, although in both cases the intravesicular contents were drastically affected. A nanowire electrochemical biosensor for the quantitative measurement of the intravesicular glutamate (Glu) content inside living neurons and its released fractions was developed. It is shown that only ca. one third to one half of intravesicular Glu molecules are released by individual vesicles during exocytotic events. The sensor opens new possibilities for exploring the regulatory mechanisms of glutamatergic neurotransmission and plasticity.